PERANAN SYAMSUL DJAFAR DALAM OPERASI DWIKORA PADA TAHUN 1964-1966 - Muhammad Afrin Yunus Hilana Nasution; Bedriati Ibrahim; Ahmal Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Syamsul Djafar is one of the military figures in the Indonesian Armed Forces Military Police who was deployed in Operation Dwikora to the Malaysian Border in 1964-1966. Syamsul Djaafar was born in Bandungrejo Village, Malang, East Java, October 19, 1942 by parents named Kardjo Kasan Darso and Tukijam Marto Gami. Syamsul Djafar was the fifth of eight children and had a role in Operation Dwikora at the Indonesia-Malaysia Confrontation. The aimed of this research is to find out and describe the events of the Indonesian Confrontation with Malaysia, to find out the life history of Syamsul Djafar, to find out the role of Syamsul Djafar in Operation Dwikora, to find out what achievements Syamsul Djafar has obtained from the government, and to find out the activities carried out by Syamsul Djafar after finishing his stint at Operation Dwikora. The data analysis used the historical writing method which consisted of several stages, namely heuristics, verification, interpretation and historiography. The result of this research is the role of Syamsul Djaafar as ABRI Military Police who was deployed in Operation Dwikora to conduct patrols along the Malaysian border and monitor the desarturs of Indonesian troops who fought in the Indonesia-Malaysia Confrontation. Before and after the completion of Operation Dwikora, Syamsul Djafar was also deployed in Operation Trikora in West Irian and Operation Seroja in East Timor. In the course of his career, Syamsul Djafar was placed in the Pekanbaru area to become the ABRI Military Police Commander and after his retirement, Syamsul Djafar became Chairman of the LVRI DPD Veterans Bachelor Corps of Riau Province.Key Words: Syamsul Djafar, Indonesia-Malaysia Confrontation, Operation Dwikora, the Role.